A proteomic approach for the identification of immunotoxic properties of Tulipalin A. Issue 23 (15th November 2016) - Zwicker, Paula; Schultze, Nadin; Niehs, Sarah; Methling, Karen; Wurster, Martina; Albrecht, Dirk; Bernhardt, Jörg; Wachlin, Gerhild; Lalk, Michael; Lindequist, Ulrike; Haertel, Beate
Abstract : The immune system is permanently exposed to several environmental influences that can have adverse effects on immune cells or organs leading to immunosuppression or inappropriate immunostimulation, called direct immunotoxicity. The natural compound Tulipalin A (TUPA), a lactone with α‐methylene‐γ‐butyrolactone moiety, can influence the immune system and lead to allergic contact dermatitis. This in vitro study focused on effects of TUPA using two immune cell lines (Jurkat T cells and THP‐1 monocytes). To evaluate the immunotoxic potential of the compound, a proteomic approach applying 2D gel electrophoresis and MALDI‐TOF/TOF‐MS in combination with metabolomic analysis was used after exposure of the cells to IC10 of TUPA. THP‐1 cells showed a strong robustness to TUPA treatment since only five proteins were altered. In contrast, in Jurkat T cells an increase in the abundance of 66 proteins and a decrease of six proteins was determined. These intracellular proteins were mapped to biological processes. Especially an accumulation of chaperones and an influence on the purine synthesis were observed. The changes in purine synthesis were confirmed by metabolomic analysis. In conclusion, the data indicate possible target processes of low doses of TUPA in Jurkat T cells and provides knowledge of how TUPA affects the functionality of immune cells.